2016
DOI: 10.1097/acm.0000000000000988
|View full text |Cite
|
Sign up to set email alerts
|

Developing Entrustable Professional Activities for Entry Into Clerkship

Abstract: The development of these EPAs indicates support for setting a standard for entry into clerkship, provides guidance for engaging preclerkship students in clinical workplace activities, and can be adapted for use by any institution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 24 publications
(8 reference statements)
0
63
0
1
Order By: Relevance
“…EPAs are core units of professional practice that can be fully entrusted to a trainee as soon as he or she has demonstrated the necessary competence to execute the activity unsupervised, and thus reflect the objectives of postgraduate training (ten Cate 2013b;ten Cate 2014). Various authors have suggested they should be suitable for undergraduate training too (Chen et al 2016;Chen et al 2015;Englander et al 2016). For example, the US Association for American Medical Colleges evoked national interest by proposing 13 EPAs that medical graduates should be able to do with limited supervision when starting residency (Englander et al 2014), as did the Canadian medical schools (Touchie and Boucher 2016).…”
Section: Introductionmentioning
confidence: 99%
“…EPAs are core units of professional practice that can be fully entrusted to a trainee as soon as he or she has demonstrated the necessary competence to execute the activity unsupervised, and thus reflect the objectives of postgraduate training (ten Cate 2013b;ten Cate 2014). Various authors have suggested they should be suitable for undergraduate training too (Chen et al 2016;Chen et al 2015;Englander et al 2016). For example, the US Association for American Medical Colleges evoked national interest by proposing 13 EPAs that medical graduates should be able to do with limited supervision when starting residency (Englander et al 2014), as did the Canadian medical schools (Touchie and Boucher 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al used this first phase to know the relevance and adequacy of the levels of competence appropriate to the context in which students develop (Chen, McNamara, et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Innovation is the newest word when it comes to medical education, as medical schools charge forward to reconfigure their curriculum. The novel vernacular is experiential learning,1 integrated approaches, and a variety of early clinical experiences 2. The overarching theme of integrated curriculum that medical schools across the USA have deployed is to create better physicians for the 21st century, with the same end result: graduating medical students at the optimal performance level when entering residency.…”
Section: Creating Physicians Of the 21st Century: Assessment Of The Cmentioning
confidence: 99%